FREQUENCY AND DERMOGRAPHIC CHARACTERISTICS OF ATOPIC DERMATITIS IN PATIENTS APPLYING TO THE ALLERGY OUTPATIENT CLINIC - Khudoyberdieva Shahnoza Iskandarovna (Scholar Express Journals, 2023)
In developing societies, allergenic diseases are increasing day by day. Food and environmental factors contribute greatly to these. We carried out this study in order to contribute to atopic dermatitis, which is the problem of the whole world.
Keywords: Atopic Dermatitis; Allergy; Family history